Determination of Reasonable Width of Filling Body for Gob-Side Entry Retaining in Mining Face with Large Cutting Height. (21st March 2022) - Pu, Shijiang; Wu, Guiyi; Liu, Qinzhi; Wang, Yuliang; Li, Qiang; Xiong, Yu
Abstract : When gob-side entry retaining is adopted in the mining face with large cutting height, due to large stope space, strong dynamic pressure, and other reasons, the filling body is usually broken and unstable due to improper width of filling body, and the stability of surrounding rock of a roadway is poor. Taking the actual project of Shaqu mine as the background, we analyze the stability factors of gob-side entry retaining with large mining height, and considering the lateral pressure and overlying load on the filling body, the mechanical model of a gob-side retaining roadway is established, the calculation method of the reserved width of the filling body is simplified, and the reasonable width of the filling body is obtained quantitatively. Through the monitoring results of numerical simulation and field test, the rationality of the calculation results of the reserved width of filling body is verified. The results show that if the width of the filling body is too small, it will not be able to bear the load of the overlying strata, resulting in the fragmentation of the filling body. The larger the width of the filling body, the greater the cutting resistance provided, which can reduce timely the stress on the roadway and above the filling body, and the more stable the retaining roadway is, but when the width increases to a certain value, the displacement of the surrounding rock of the roadway has changed little. When the width of the filling body is 4 m, the stability of gob-side entry retaining can be guaranteed.